ESTUDO DA CORRELAÇÃO ENTRE QUALIDADE DE VIDA E FUNÇÕES RESPIRATÓRIAS EM MULHERES PORTADORAS DE DOENÇA PULMONAR OBSTRUTIVA CRÔNICA - Mangueira, Nilton Maciel (2007)
Introduction: The quality of life (QOL) of patients with Chronic Obstructive Pulmonary Disease (CPOD) is influenced by its impact on daily activities, due to the damage of the respiratory functional capacity. Objective: Correlate the QOL of women who carrying COPD with the respiratory functions and the 6 minutes walk test (6MWT). Methods: A cross study of 30 women with light or moderate COPD was carried out at the Pneumology Ambulatory care facility of the University Hospital, Presidente Dutra of the Maranhão State Federal University. The Saint George’s Respiratory Questionnaire (SGRQ) in the Respiratory Disease was used, to evaluate the measures of maximum respiratory pressures, spirometry and the 6MWT. Besides the descriptive statistics was realized the test t Student to dependent variables and the Linear Coefficient of Pearson for the correlation studies. Results: The QOL was altered in 96,7% of the studied patients in all sections of the SGRQ. The average distance (317,69 m) covered on the 6MWT, as well as the inspiratory muscular force (-53,48 cmH2O) and expiratory (69,55 cmH2O), were below the expected values for the normality. There was no correlation of the QOL with the BMI nor with the pulmonary function. The domains impact and the activities of the SGRQ presents negative correlation with age and positive with the Borg Scale. The domain impact still had correlation with the PImáx and the 6MWT. Conclusion: The patients with COPD of the study had presented a linear correlation among the QOL of the SGRQ and the variables of age, PImáx and the Borg Scale, still the low QOL in all the sections of the SGRQ, low performance on the 6MWT and reduced respiratory muscular force.